Urinary Tract Infection with Obstructional Pyelonephritis in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In this article, the author provides an analysis of the results of surgical treatment of urinary tract pathologies in children affected by pyelonephritis. A qualitative analysis of the microbial landscape of pathogens causing urinary tract infections in children is carried out.